Experimental study of nanoparticle transport and penetration efficiency on a sharp-bent tube (elbow connection). (July 2020) - Kwak, Dong-Bin; Kim, Seong Chan; Lee, Handol; Pui, David Y.H.
Highlights: Nanoparticle penetration through a sharp-bent tube was examined. Effects of particle sizes and flow rates on penetration were investigated. Diffusion loss was dominant in low Schmidt number. Secondary flow was enhanced by high Reynolds number. Empirical correlation curve as a function of Peclet number was obtained. Abstract: In the present study, nanoparticle transport through a sharp-bent tube, i.e., elbow connection, was systematically examined by using a particle size ranging from 3 to 50 nm. In the experiments, particle size and flow rate significantly affected the penetration efficiency. To be specific, the smaller particles which had higher diffusion coefficient were more likely deposited on the sharp-bent tube and the higher flow rate reduced the flow-directional nanoparticle residence time resulting in increased penetration efficiency. To explain the experimental penetration efficiency on the sharp-bent tube, characteristics of fluid flow on the sharp-bent tube were studied numerically. The flow field calculations showed that the recirculation pattern occurred at the corner of the sharp-bent tube, and the flow separation and reattachment were observed at the inner wall right after the bending point. Additionally, when compared to higher Reynolds number, the intensity of the secondary flow was weaker at lower Reynolds number as well as its center point was located farther from the tube wall. Therefore, the nanoparticle residence time on the sharp-bent tube became longer and a smaller number of particles penetrated the tube at lower Reynolds number. Based on the experimental data, the penetration efficiency on the sharp-bent tube was predicted by the correlation fitting curve. The relative penetration efficiency on the sharp-bent tube was also obtained by comparing it to the penetration efficiency on the straight tube. The strong diffusion transport rate and weak advection transport rate induced more particle losses due to secondary flow after bending point, resulting in the decreased relative particle efficiency.